Review: Biological relevance of disseminated tumor cells in cancer patients - Riethdorf, Sabine; Wikman, Harriet; Pantel, Klaus (International journal of cancer, 2008)
The prognosis of cancer patients is largely determined by the occurrence of distant metastases. In patients with primary tumors, this relapse is mainly due to clinically occult micrometastasis present in secondary organs at primary diagnosis but not detectable even with high resolution imaging procedures. Sensitive and specific immunocytochemical and molecular assays enable the detection and characterization of disseminated tumor cells (DTC) at the single cell level in bone marrow (BM) as the common homing site of DTC and circulating tumor cells (CTC) in peripheral blood. Because of the high variability of results in DTC and CTC detection, there is an urgent need for standardized methods. In this review, we will focus on BM and present currently available methods for the detection and characterization of DTC. Furthermore, we will discuss data on the biology of DTC and the clinical relevance of DTC detection. While the prognostic impact of DTC in BM has clearly been shown for primary breast cancer patients, less is known about the clinical relevance of DTC in patients with other carcinomas. Current findings suggest that DTC are capable to survive chemotherapy and persist in a dormant nonproliferating state over years. To what extent these DTC have stem cell properties is subject of ongoing investigations. Further characterization is required to understand the biology of DTC and to identify new targets for improved risk prevention and tailoring of therapy. Our review will focus on breast, colon, lung, and prostate cancer as the main tumor entities in Europe and the United States. © 2008 Wiley‐Liss, Inc.